Cultural Equivalence and Humor: Analyzing the Translation Procedures in the Indonesian Version of Matilda - Priska Adisti Anggitaning Widhi (Institute of Research and Community Outreach - Petra Christian University, 2026)
This research analyses the translation procedures of humor in Roald Dahl's novel Matilda from English to Indonesian, focusing on how these procedures maintain or alter the humorous effect for child readers. Utilising Peter Newmark's translation theory, particularly his concepts of translation methods and various translation procedures, the study employs a qualitative descriptive-comparative approach. The primary data source comprises the English original and the Indonesian translated version of Matilda. Findings indicate that the translator predominantly uses Literal Translation for universally visual and hyperbolic humor, while relying heavily on Adaptation, Cultural Equivalent, Compensation, and Expansion for wordplay, cultural references, or ambiguous humor. The analysis reveals a dynamic balance between communicative and semantic methods, generally succeeding in preserving Dahl's unique, often dark, humor for Indonesian child readers. Despite some instances of reduction, the core comedic effect is largely retained, highlighting the crucial role of adaptive procedures in ensuring cross-cultural humor transfer in children's literature.